2012
DOI: 10.1097/ico.0b013e31823d03e3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Penetrating Keratoplasty for Keratoconus With Resolved Corneal Hydrops

Abstract: Although endothelial rejection episodes are more common in eyes with resolved corneal hydrops, long-term allograft survival and visual results after PK in eyes with keratoconus are excellent, irrespective of prior corneal hydrops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 24 publications
0
22
0
3
Order By: Relevance
“…Most recently, it was found that keratoconic eyes with prolonged hydrops (ie, .3 months) and/or those with coexistent ocular allergy were more prone to postgraft endothelial rejection. 22 Neovascularization also compromises the physiologic corneal immune privilege, potentially doubling the risk of allograft rejection. [23][24][25] The presence of seasonal allergic conjunctivitis, protracted clinical course of the hydrops, and development of corneal neovascularization are therefore significant negative prognostic factors for the longevity of any transplant for this child.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, it was found that keratoconic eyes with prolonged hydrops (ie, .3 months) and/or those with coexistent ocular allergy were more prone to postgraft endothelial rejection. 22 Neovascularization also compromises the physiologic corneal immune privilege, potentially doubling the risk of allograft rejection. [23][24][25] The presence of seasonal allergic conjunctivitis, protracted clinical course of the hydrops, and development of corneal neovascularization are therefore significant negative prognostic factors for the longevity of any transplant for this child.…”
Section: Discussionmentioning
confidence: 99%
“…Features of corneal hydrops seen on histopathology, and more recently using anterior segment optical coherence tomography, include epithelial and stromal edema, intrastromal fluid clefts, and changes in the DM (Figure 2). The DM can show detachment from the stroma with or without breaks and flat or rolled ends 54,55…”
Section: Pathologymentioning
confidence: 99%
“…Severe complications of corneal hydrops are infrequent but include extensive corneal scarring, severe neovascularisation, epithelial defects, microbial keratitis, corneal perforation and glaucoma . A history of hydrops may also predispose subjects to greater likelihood of episodes of endothelial graft rejection after penetrating keratoplasty …”
mentioning
confidence: 99%